PENGEMBANGAN MEDIA EPIK (ENSIKLOPEDIA PANCASILA INTERAKTIF DAN KREATIF) MATERI PANCASILA DALAM DIRIKU UNTUK KELAS IV SEKOLAH DASAR - Hendri, Nurhikmah Amelia Putri; Ramadan, Zaka Hadikusuma (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to examine the development process of the EPIK (Interactive and Creative Pancasila Encyclopedia) media to ensure its validity. The research employed the ADDIE development model. Primary data were obtained from teachers, students, and validators, while secondary data were sourced from books, articles, and relevant previous studies. Data collection instruments included interview guide sheets and validation questionnaires from material experts, language experts, media experts, as well as response questionnaires from teachers and students. Data were analyzed qualitatively based on feedback and comments, and quantitatively based on validation scores and user responses. The validation results indicated that the EPIK media falls into the “very valid” category without requiring revision. The material aspect scored 88.8%, the language aspect 98.8%, and the media aspect 97.6%, all categorized as very valid. Teachers’ and students’ responses reached an average score of 100%, categorized as “excellent.” Therefore, the EPIK media is considered feasible for use as a learning medium for Pancasila in elementary schools, as it meets the criteria of content, language, and media validity, and receives positive user responses.